Effects of horseback riding exercise therapy on hormone levels in elderly persons - Cho, Sung-Hyoun (J Phys Ther Sci, 2015)
[Purpose] The purpose of this study was to investigate the effect of riding exercise on hormone levels in normal elderly people who were taught horseback riding for 8 weeks. [Subjects] Subjects were classified into an exercise group (n=10) and control group (n=10). [Methods] The two groups, horseback riding exercise group of 10 and control group of 10, were each tested for 15 minutes, 3 times, over 8 weeks. Post-exercise tests were implemented in both groups in the same way as pre-study tests. [Results] The horseback riding group showed a significant difference in the pre- and post-exercise serotonin and cortisol levels. Additionally, serotonin and cortisol levels showed significant differences between the two groups. [Conclusion] Serotonin and cortisol levels significantly increased in the experimental group, suggesting that horseback riding exercise is effective for improving the levels of these hormones.